SPATIAL ANALYSIS OF SHORELINE CHANGES IN THE COASTAL OF SUBANG DISTRICT, WEST JAVA - Ankiq Taofiqurohman; M. Furqon Azis Ismail (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
ABSTRACT Observation of coastal shoreline changes in the Subang District was conducted using Digital Shoreline Analysis System Program based on the satelite images of Landsat TM from 1996 to 2010. The purpose of this study was to determine the distance of shoreline change. Methods used in this study were field survey and regression analysis of shoreline data. The results of this study indicated the existence of a region experiencing accretion and abrasion. The maximum width of accretion of the coast was 1,051.55 meter while the maximum abration was 1,206.83 meter. Coastal shoreline change in Subang District occurred mainly due to the development activities such as residential construction, altering the coastal mangrove to ponds and rice paddies, and sediment transport from the river around Subang District. Keywords: shoreline, Subang District, satelite images, accretion, abration